Scottish engineering contracts - Parry, Gareth (Thomas Telford, 2003)
A basic guide to the principles of Scots law as they relate to engineering contracts and day to day operations and practices. It also reviews key features of commonly used standard forms of engineering contracts, such as the ICE Conditions of Contract 7th Edition and the CECA Form of Sub-Contract.